A Novel Reconstruction Approach After Skin Cancer Ablation Using Lateral Arm Free Flap: A Serial Case Report - Soyeon Jung; Seungjun Lee; Seokchan Eun (Medicina)
Background and Objectives: The lateral arm flap has been a very useful choice for the reconstruction of small to medium-sized defects, such as in the hands, extremities, and oral head and neck area. Its versatile characteristics and surgical feasibility allow this flap to be widely applied, but its reconstructive potential in the facial subunit after tumor ablation procedures has never been reported. In this study, we aimed to utilize the advantages of this flap to carry out facial temple subunit defect reconstruction. Materials and Methods: Between 2020 and 2023, 12 patients underwent temple reconstruction with lateral arm free flaps after wide malignant tumor excisions. There were seven women and five men, and the mean patient age was 60.6 years. Among the patients with cancer, six had squamous cell carcinoma, five had basal cell carcinoma, and one had myxofibrosarcoma. All flaps were elevated under general anesthesia. Alprostadil (PGE1, Eglandin®, Mitsubishi Tanabe Korea, Seoul, Republic of Korea) was administered postoperatively. Results: All flaps were the fasciocutaneous type, with sizes that varied from 3 cm × 4 cm to 5 cm × 7 cm (average size: 22.7 cm2). The average pedicle length was 6.1 cm. The versatility of the lateral arm flap enabled successful coverage in all cases, with no specific complications. Good functional outcomes and good ranges of motion in the donor arms were observed after surgery. Conclusions: The authors successfully verified the advantages of lateral arm flaps in the treatment of medium-sized facial temple subunit defects.